Relevansi Nilai Kepentingan Non Pengendali dalam Laporan Keuangan Konsolidasi: Bagaimana Pasar Bereaksi dan Kemampuannya dalam Memprediksi Laba dan Dividen? - Kusuma, Marhaendra; Hilda Agustin, Beby (Jurnal Akuntansi dan Governance, 2024)
Objectives: This study investigates alterations in the presentation of consolidated financial statements concerning profit and equity information associated with non-controlling interests. The primary aim is to establish the significance of attributing value to non-controlling interests and assess the necessity of providing such attribution? Design/method/approach: The research adopts a methodology that verifies the relevance of attributive value by examining the impact of profits and equity attributable to non-controlling interests on stock returns, t+1 comprehensive income, and t+1 dividends. The analysis is conducted using data from 504 companies listed on the Indonesia Stock Exchange (IDX) over the period 2015 to 2021, totaling 3,528 observation data points.Results/findings: The results indicate that net profit, comprehensive profit, and equity attributable to non-controlling interests exhibit value relevance. These findings are substantiated by their significant influence on stock returns, t+1 dividends, and t+1 comprehensive income. Theoretical contribution: This study contributes to the literature by affirming that profit and equity attribution policies possess value relevance. Despite the extended nature of consolidated financial statements, they do not pose difficulties for users in interpretation; instead, they enhance clarity regarding the distribution of profits and equity among different types of owners. Presenting non-controlling interests in a manner that reflects care, transparency, and fairness of information caters to the needs of minority owners. Practical contribution: The study suggests that potential investors with minor shareholdings can predict investment returns more accurately by considering attributable profits and equity rather than aggregate figures.Limitations: This study does not directly examine the impact of profits attributable to non-controlling interests on dividends received by shareholders with non-controlling interests